(untitled) - Keur, Christian (Atlanta, GA, 2015)
iOS Programming: The Big Nerd Ranch Guide leads you through the essential concepts, tools, and techniques for developing iOS applications. After completing this book, you will have the know-how and the confidence you need to tackle iOS projects of your own. Based on Big Nerd Ranch's popular iOS Bootcamp course and its well-tested materials and methodology, this bestselling guide teaches iOS concepts and coding in tandem. The result is instruction that is relevant and useful.
Keywords: iOS (nguồn điện),iPhone (Smartphone),Phần mềm ứng dụng,iOS (Electronic resource),iPhone (Smartphone),Application software; Chương trình,Chương trình,Phát triển,Programming,Programming.,Development